Avanços na investigação de componentes M e de descargas atmosféricas ascendentes por meio de registros sincronizados de campo elétrico, de corrente e de vídeos - Listz Simoes de Araujo (2013)
This work describes recent scientific contributions to the knowledge of the lightning, developed in the context of this master thesis. Notably, original results and conclusions with regard to M-components of negative downward lightning and to upward lightning are presented. Relevant interpretations and conclusions were developed from the synchronized records of electric field, current, video and luminosity of lightning channels, all obtained at Morro do Cachimbo Station. Regarding the M-Components of natural lightning, their currents were never measured before this work. From the several obtained records, it was observed that all the parameters of this event are relatively similar with those from triggered lightning. Moreover, it was verified that these M-Components occur frequently in first strokes, different from the usual assumption in the international literature. With respect to upward lightning, the first measurements of this event performed in tropical regions are also presented. The parameters of all upward lightning measured at Morro do Cachimbo Station are somewhat similar to those from temperate regions, though the geometric mean of the total transferred charge measured in the latter is about five times larger than the former. Besides, results related to the improvement of a special lightning current meter developed by the LRC researchers, yielded in the context of this thesis are presented.